Visualizing article history on Wikipedia - An exploratory design study - Andersson, Henrik; Eliasson, Christofer (My University, 2011)
The aim of this project was to make the historical content of Wikipedia articles visual and easily accessible to the Wikipedia users. By doing this, the goal was to make it possible for users to see, while reading an article, how it has evolved over time. Based on the design results, an interactive prototype was to be built, demonstrating the results. There were three main objectives for the design, stating that users should be able to see how much an article has been edited, how many have contributed to it, and if some have contributed more than others. The project was performed as an exploratory design study, using methods such as the 6-3-5- method, extreme characters, personas and prototyping. During the design process, several challenges arose, such as; what metaphor to base the design on; how to use the screen space most efficiently; how to visualize what has been done by different contributors; and, how to distinguish live content from historical content. When a final design was reached, it was implemented into an interactive prototype, which could be used live on Wikipedia, thereby fulfilling the aim and the main objectives of the project. Some of the main features in the final design includes; dividing historical content into smaller parts based on articles subtopics; distinguishing different contributor types; making the visualization available for the users while reading an article; and providing access to the historical content, making it possible to view it while reading article. Making the history of an article easily accessible have several possible benefits. One such benefit is that it could make it easier for users to value the content in terms of trustworthiness. Easier access to historical content has been requested in previous studies, and after this project, we see no reason to doubt the benefits put forward in those studies.
Keywords: Information Technology; Informationsteknik